In vitro biocompatibility evaluation of functional electrically stimulating microelectrodes on primary glia - Tsui, Christopher T.; Mirkiani, Soroush; Roszko, David A.; Churchward, Matthew A.; Mushahwar, Vivian K.; Todd, Kathryn G. (Frontiers in Bioengineering and Biotechnology, 2024)
Neural interfacing devices interact with the central nervous system to alleviate functional deficits arising from disease or injury. This often entails the use of invasive microelectrode implants that elicit inflammatory responses from glial cells and leads to loss of device function. Previous work focused on improving implant biocompatibility by modifying electrode composition; here, we investigated the direct effects of electrical stimulation on glial cells at the electrode interface. A high-throughput in vitro system that assesses primary glial cell response to biphasic stimulation waveforms at 0 mA, 0.15 mA, and 1.5 mA was developed and optimized. Primary mixed glial cell cultures were generated from heterozygous CX3CR-1 +/EGFP mice, electrically stimulated for 3 days using 75 μm platinum-iridium microelectrodes, and biomarker immunofluorescence was measured. Electrodes were then imaged on a scanning electron microscope to assess sustained electrode damage. Fluorescence and electron microscopy analyses suggest varying degrees of localized responses for each biomarker assayed (Hoescht, EGFP, GFAP, IL-1β), a result that expands on comparable in vivo models. This system allows for the comparison of a breadth of electrical stimulation parameters, and opens another avenue through which neural interfacing device developers can improve biocompatibility and longevity of electrodes in tissue.